Prescription Patterns and Drug Use Indicators in a Nigerian Urban Tertiary Health Care Facility - Ogunleye, Olayinka O.; Modupe R. Oyawole; Adesola F. Yinka-Ogunleye, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
Rationale use of drugs increases the quality of health care, ensures cost effectiveness in health care delivery and better therapeutic outcomes. It however remains a problem in most parts of the world especially in the developing nations. This study was carried out to describe the pattern of drug utilization in a Nigerian Urban Tertiary Health Care Facility and evaluate the quality of prescriptions. This was a cross sectional study of all prescriptions received at the Pharmacy Department of the Lagos State University Teaching Hospital, Nigeria for the month of November, 2013. All prescriptions were analyzed for some standard indices of rationale prescription. Descriptive Statistics were done using SPSS version 17.0. There were 7,516 encounters with a total of 14,794 drugs prescribed. The mean number of drugs per encounter was 2.3+1.4 drugs. Practically all classes of drugs were represented with Antibiotics being the most prescribed (26.2%), followed by Analgesics (19.4%) and Antihypertensive drugs (10.4%) respectively. Only 47.8% drugs were prescribed using generic name while there were 25% encounters with injections. The percentage prescription from the Essential Medicines Lists of the hospital was 27.9%. There were deficiencies in the quality of drug prescriptions studied as well as indices of irrational use of medicines among the prescribers. Appropriate measures needs be identified and implemented to improve on the use of medicine.